Simultaneous doping of sulfur and chloride ions into ZnO nanorods for improved photocatalytic properties towards degradation of methylene blue. Issue 4 (15th February 2022) - Ujjan, Zaheer Ahmed; Bhatti, Muhammad Ali; Shah, Aqeel Ahmed; Tahira, Aneela; Shaikh, Nek Muhammad; Kumar, Shusheel; Mugheri, Abdul Qayoom; Medany, Shymaa S.; Nafady, Ayman; Alnjiman, Fahad; Emo, Mélanie; Vigolo, Brigitte; et al.
Abstract: In this study, we have successfully doped sulfide (S −2 ) and chloride (Cl −1 ) simultaneously into ZnO by hydrothermal method. The structure, morphology, composition, and optical properties of the prepared S–Cl doped ZnO nanostructures were investigated by x-ray diffraction (XRD), scanning electron microscopy (SEM), scanning transmission electron microcopy (STEM), energy dispersive spectroscopy (EDX) and UV–visible (UV–Vis) spectroscopy techniques. After, doping of both S and Cl into ZnO no significant alteration in the nanorod morphology was noticed. The wurtzite crystal structure of ZnO was retained with a red shift in the 2Ɵ towards high angle. The XRD results are supported by the high-resolution transmission electron microscopy. The elemental analysis revealed a successful doping of S and Cl into ZnO structure. Importantly, the optical band gap of ZnO was decreased 2.9 eV upon doping of S and Cl ions. Thus, the nonmetal doping via S and Cl has significantly enhanced the photocatalytic properties of ZnO towards methylene blue (MB) due to high density of active sites and decreased charge recombination rate of electron-hole pairs. The photo-degradation efficiency towards MB reached 99.64% upon using S and Cl doped ZnO photocatalyst using optimum dose of 15 mg and initial dye concentration of 1.87 × 10 −6  M. The use of simultaneous nonmetal doping concept could of great importance for the preparation of other nanostructured materials and their use in potential applications like solar cells, and photoelectrochemical water splitting.